Climate Change and Energy Sustainability. Which Innovations in European Strategies and Plans - Rocco Papa; Carmela Gargiulo; Floriana Zucaro (TeMA: Journal of Land Use, Mobility and Environment, 2014)
In recent years, the effects of climate change on urban areas have pushed more and more policy-makers and urban planners to deal with the management of territorial transformations in a systemic and multi-sector perspective, due to the complexity of the issue. In order to enhance the urban governance of climate change and cope with environmental sustainability, the concept of resilience can be used. In this perspective, the present work has a double purpose: on the one hand to reflect on he need to adopt a new comprehension/interpretive approach to the study of the city, which embraces the concept of resilience, and on the other hand to perform a reading of European strategies and plans oriented to mitigate the effects of climate change and to achieve the goals of energy and environmental sustainability. This paper describes some of the results of the knowledge framework of the Project Smart Energy Master for the energy management of territory financed by PON 04A2_00120 R & C Axis II, from 2012 to 2015 aimed at supporting local authorities in the development of strategies for the reduction of energy consumption through actions designed to change behavior (in terms of use and energy consumption) and to improve the energy efficiency of equipment and infrastructure. The paper is divided into three parts: the first is oriented to the definition of the new comprehension/interpretive approach; the second illustrates a series of recent innovations in planning tools of some European States due to the adoption of the concept of resilience; the third, finally, describes and compares the most innovative energy and environmental strategies aimed at contrasting and/or mitigate the effects of climate change, promoted in some European and Italian cities.